Tin Mineralization in Tanjung Genting Sandstone, Terap Village, Bangka Belitung Islands Province - Esra Deliana Sihombing; Hari Wiki Utama; Yudi Arista Yulanda (EKSPLORIUM, 2025)
The research area is located in Terap Village, Tukak Sadai District, South Bangka Regency, Bangka Belitung Islands Province. The research was conducted at PT Timah Tbk. The purpose of this study was to understand the geology of the study area and the mineralization present, as well as the rocks that serve as the source of mineralization in the study area. The methodology used in this study was direct geological mapping and laboratory analysis in the form of petrography, XRF, XRD, and mineragraphy. The stratigraphy obtained included the Tanjung Genting sandstone unit, the Klabat granite intrusion, and alluvial sediment units. The petrographic analysis revealed quartz wacke and lithic wacke. Portable XRF analysis revealed a tin content of 2183 ppm. The XRD analysis revealed clay minerals in the form of goethite, quartz, kaolinite, muscovite, and illite. The mineragraphy analysis revealed cassiterite and hematite mineralization. The research concludes that this mineralization can be grouped into the greisenized deposit type, with the Cassiterite + Hematite mineral group only found in the mineralization zone with the highest Sn element content obtained in the research area of 2183 ppm.